APPLICATION OF CERTAINTY FACTOR METHOD FOR ANALYSIS OF PESTS AND DISEASES OF SPINACH PLANTS AT THE AGRICULTURAL OFFICE OF ASAHAN DISTRICT - Fuji Rahayu; Raja Tama Andri Agus; Suparmadi Suparmadi (Jurnal Teknik Informatika (Jutif), 2022)
Pests and diseases are organisms that interfere with plant cultivators so that plant growth and development is hampered. Currently pests and diseases on spinach plants are very varied, one of the pests and diseases of spinach plants is leaf caterpillar and white rust disease where the attack on the leaves is hollow and the formation of white spots on the spinach plant. The problem that occurs is that spinach plant pests and diseases are often experienced by spinach cultivators. This is because some farmers still lack information and still have difficulty distinguishing between pests and diseases. Therefore, mistakes are often made to overcome existing pests and diseases. It takes an expert who can provide the best solution for farmers but is limited to an expert, so to deal with these problems an expert system is designed using the Certainty Factor (CF) method. This study uses the Certainty Factor (CF) method to overcome the problems that exist in spinach plants, in this case the data used consists of 7 data and 14 symptoms that attack spinach plants. Each symptom has a weight obtained from the expert describing the possibility of the occurrence of symptoms of a pest and disease. Based on the results of the study obtained a percentage of 70% accuracy or confidence level based on system calculations and manual calculations.